2018
DOI: 10.1002/ajmg.b.32698
|View full text |Cite
|
Sign up to set email alerts
|

Italian validation of the functional difficulties questionnaire (FDQ‐9) and its correlation with major determinants of quality of life in adults with hypermobile Ehlers–Danlos syndrome/hypermobility spectrum disorder

Abstract: The 2017 Nosology defines the new criteria for hypermobile Ehlers-Danlos syndrome (hEDS), which is now considered one end of a continuous spectrum encompassing isolated, non-syndromic joint hypermobility (JH) and hypermobility spectrum disorders (HSD). Preliminary data indicate a link between JH and neurodevelopmental disorders and, in particular, developmental coordination disorder (DCD) in children. Assessing DCD in adults is difficult and the recently described functional difficulties questionnaire 9 (FDQ-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Almost 20% of the subjects revealed a severely impaired quality of life in mental health and social functioning. This finding is consistent with Morlino et al [38] who found a significant reduction in QoL and a significant association with functional difficulties. Additionally, they observed that the number of painful joints was a predictor of functional impairment.…”
Section: Discussionsupporting
confidence: 92%
“…Almost 20% of the subjects revealed a severely impaired quality of life in mental health and social functioning. This finding is consistent with Morlino et al [38] who found a significant reduction in QoL and a significant association with functional difficulties. Additionally, they observed that the number of painful joints was a predictor of functional impairment.…”
Section: Discussionsupporting
confidence: 92%
“…The discreetly high incidence of chronic fatigue observed in our cEDS cohort is in line with previous observations that emphasized that in EDS this issue is more common than in the general population and likely contributes to the patients' functional impairment, psychological distress, and decreased QoL [86][87][88][89]. Like in the general population, in cEDS fatigue is multifactorial with contributing factors including articular pain, headache, sleep disturbance, and abnormally low blood pressure often associated with postural orthostatic tachycardia syndrome (POTS) or neurally mediated hypotension (NMH), nutritional deficiency, medications, and/or allergies (present in 32% of our patients) [80,81,87,[90][91][92][93][94][95]. Cerebrospinal fluid leak, which has been reported in cEDS as a cause of postural hypotension and headache [96], was not diagnosed in our cohort (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Sixth, we could not distinguish between HSD and hEDS, but because of the extensive clinical overlap between the two, 38 previous studies suggested that they should be addressed, for clinical and research purposes, as one group 39 . Recent studies that explored other comorbidities of HSD and hEDS grouped the two conditions in a single phenotype termed HSD/hEDS 40–42 . The strengths of this study include its nationwide sample, systematic collection of medical, psychiatric, and socioeconomic data, and routine screening of adolescents for migraine and HSD/hEDS.…”
Section: Discussionmentioning
confidence: 99%